2016
DOI: 10.1186/s40168-016-0198-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid change of fecal microbiome and disappearance of Clostridium difficile in a colonized infant after transition from breast milk to cow milk

Abstract: Background Clostridium difficile is the most common known cause of antibiotic-associated diarrhea. Upon the disturbance of gut microbiota by antibiotics, C. difficile establishes growth and releases toxins A and B, which cause tissue damage in the host. The symptoms of C. difficile infection disease range from mild diarrhea to pseudomembranous colitis and toxic megacolon. Interestingly, 10–50 % of infants are asymptomatic carriers of C. difficile. This longitudinal study of the C. difficile colonization in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 57 publications
4
57
0
1
Order By: Relevance
“…The cessation of milk oligosaccharides and the addition of solid foods results in a 10 to 100 percent decline in the abundance of bifidobacterium and an increase in the numbers of commensal clostridium and bacteroides (Bergstrom et al, 2014;Backhed et al, 2015;Davis et al, 2016;Khonsari et al, 2016). Work done by Bakhed and associates (Backhed et al, 2015) suggests that the cessation of breast-feeding is the major contributor to the functional shift in the gut microbiome.…”
Section: The Effect Of Dietary Changes On the Gut Microbiota In The Fmentioning
confidence: 99%
“…The cessation of milk oligosaccharides and the addition of solid foods results in a 10 to 100 percent decline in the abundance of bifidobacterium and an increase in the numbers of commensal clostridium and bacteroides (Bergstrom et al, 2014;Backhed et al, 2015;Davis et al, 2016;Khonsari et al, 2016). Work done by Bakhed and associates (Backhed et al, 2015) suggests that the cessation of breast-feeding is the major contributor to the functional shift in the gut microbiome.…”
Section: The Effect Of Dietary Changes On the Gut Microbiota In The Fmentioning
confidence: 99%
“…Previous studies have reported that children in the youngest age groups may be protected by several mechanisms such as maternal antibodies and breastfeeding (15,16). It is possible that after the age of 6 months, with the introduction of supplementary foods and changing nutritional habits, this protection declines (17,18). Additionally, the risk of placing contaminated fingers and fomites in the mouth is substantially increased owing to physiological changes like teething and crawling which begin at this age (19).…”
Section: Discussionmentioning
confidence: 99%
“…In circumstances when Clostridium difficile, the most common known cause of antibiotic-associated diarrhea, is present, this bacterium can disappear over early development, in the absence of any symptoms (57). This is unusual, as at later developmental time-points antibiotic-induced increases in C. difficile lead to the release of toxins A and B, which cause significant tissue damage in the host, with symptoms that range from mild diarrhea to pseudomembranous colitis and toxic megacolon.…”
Section: Breastfeeding: Modulation Of the Gut And Gut-brain Axismentioning
confidence: 99%